2017
DOI: 10.1371/journal.pone.0174738
|View full text |Cite
|
Sign up to set email alerts
|

A post-GWAS analysis of predicted regulatory variants and tuberculosis susceptibility

Abstract: Utilizing data from published tuberculosis (TB) genome-wide association studies (GWAS), we use a bioinformatics pipeline to detect all polymorphisms in linkage disequilibrium (LD) with variants previously implicated in TB disease susceptibility. The probability that these variants had a predicted regulatory function was estimated using RegulomeDB and Ensembl’s Variant Effect Predictor. Subsequent genotyping of these 133 predicted regulatory polymorphisms was performed in 400 admixed South African TB cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
(56 reference statements)
0
14
1
Order By: Relevance
“…TB-associated innate immune genes encode pattern recognition receptors, inflammatory factors, nuclear receptors, surfactant proteins, oxidative response proteins, cytokines, chemokines, etc., (Azad et al, 2012;Fol et al, 2015). A majority of TB-associated SNPs have been derived from GWAS, taking advantage of massive genomics data sets across populations, leading to inferences of candidate genes contributing to human immune variation and susceptibility or resistance to diseases in general (Uren et al, 2017). However, GWAS-significant SNPs mostly do not reveal the underlying mechanisms of a potential functional variant or even the causative genes, as regulatory variants can reside at a long distance from their target genes, acting by chromatin looping mechanisms (Sadee et al, 2014;Gallagher and Chen-Plotkin, 2018).…”
Section: Human Genetic Polymorphisms In Tb-associated Innate Immune Gmentioning
confidence: 99%
“…TB-associated innate immune genes encode pattern recognition receptors, inflammatory factors, nuclear receptors, surfactant proteins, oxidative response proteins, cytokines, chemokines, etc., (Azad et al, 2012;Fol et al, 2015). A majority of TB-associated SNPs have been derived from GWAS, taking advantage of massive genomics data sets across populations, leading to inferences of candidate genes contributing to human immune variation and susceptibility or resistance to diseases in general (Uren et al, 2017). However, GWAS-significant SNPs mostly do not reveal the underlying mechanisms of a potential functional variant or even the causative genes, as regulatory variants can reside at a long distance from their target genes, acting by chromatin looping mechanisms (Sadee et al, 2014;Gallagher and Chen-Plotkin, 2018).…”
Section: Human Genetic Polymorphisms In Tb-associated Innate Immune Gmentioning
confidence: 99%
“…To date, nine GWAS studies have been published in PTB (summarized in Table 1 of Uren et al [9]). A 2010 study discovered an association in a gene desert on chromosome 18q11.2 in a combined Ghanaian, Gambian and Malawian cohort [41].…”
Section: Previous Genetic Studies Of Tbmentioning
confidence: 99%
“…With few exceptions [21, 23, 50], most previous genetic association studies have not considered genes as part of pathways Using the 15 genes and 36 genes identified by candidate literature review and GWAS literature review (the latter as described in Table 1 and do overlap with some of the candidate genes [9]), respectively, we used Ingenuity Pathway Analysis (IPA) (Qiagen) to determine if any pathways were enriched using all genes from our list. IPA mapped all genes from our provided list onto expert-curated canonical pathways from the Ingenuity Knowledge Base.…”
Section: Pathway Enrichment From Gene Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing sputum culture-confirmed pulmonary TB (PTB) as the phenotype, there are ten GWAS studies published to date (44). Two studies from Ghana and the Gambia identified two variants.…”
Section: Clinical Tb Diseasementioning
confidence: 99%